Stepping Stones or Second Class Donors?: a qualitative analysis of gay, bisexual, and queer men's perspectives on plasma donation policy in Canada - Daniel Grace; Mark Gaspar; Benjamin Klassen; David Lessard; Praney Anand; David J. Brennan; Nathan Lachowsky; Barry D. Adam; Joseph Cox; Gilles Lambert; Jody Jollimore; Trevor A. Hart (BMC, 2021)
Abstract Background Men who have sex with men (MSM) are not eligible to donate blood or plasma in Canada if they have had sex with another man in the last 3 months. This time-based deferment has reduced since 2013; from an initial lifetime ban, to five-years, one-year, and now three-months. Our previous research revealed that gay, bisexual, queer, and other MSM (GBM) supported making blood donation policies gender-neutral and behaviour-based. In this analysis, we explored the willingness of Canadian GBM to donate plasma, even if they were not eligible to donate blood. Methods We conducted in-depth interviews with 39 HIV-negative GBM in Vancouver (n = 15), Toronto (n = 13), and Montreal (n = 11), recruited from a large respondent-driven sampling study called Engage. Men received some basic information on plasma donation prior to answering questions. Transcripts were coded in NVivo following inductive thematic analysis. Results Many GBM expressed a general willingness to donate plasma if they became eligible; like with whole blood donation, GBM conveyed a strong desire to help others in need. However, this willingness was complicated by the fact that most participants had limited knowledge of plasma donation and were unsure of its medical importance. Participants' perspectives on a policy that enabled MSM to donate plasma varied, with some viewing this change as a "stepping stone" to a reformed blood donation policy and others regarding it as insufficient and constructing GBM as "second-class" donors. When discussing plasma, many men reflected on the legacy of blood donor policy-related discrimination. Our data reveal a significant plasma policy disjuncture-a gulf between the critical importance of plasma donation from the perspective of Canada's blood operators and patients and the feelings of many GBM who understood this form of donation as less important. Conclusions Plasma donor policies must be considered in relation to MSM blood donation policies to understand how donor eligibility practices are made meaningful by GBM in the context of historical disenfranchisement. Successful establishment of a MSM plasma donor policy will require extensive education, explicit communication of how this new policy contributes to continued/stepwise reform of blood donor policies, and considerable reconciliation with diverse GBM communities.